2021
DOI: 10.1088/1361-6528/ac0470
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity and mechanical performance of hexagonal boron nitride nanosheets-based epoxy adhesives

Abstract: Thermosets possess diverse physical and chemical properties and thus they are widely used in various applications such as electronic packaging, construction, and automotive industries. However, their poor thermal conductivity and weak mechanical performance jeopardize their continual spread in modern industry. In this study, boron nitride nanosheets (BNNSs) were employed to promote both mechanical and thermal properties of epoxy nanocomposites. BNNSs and their epoxy nanocomposites were fabricated using in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…GO causes rigidity enhancement of the PVA chain to restrict the movement of the molecular chains, leading to a high Young's modulus [46,47]. Tensile strength and elongation at break commonly drop after a certain weight percentage while the Young's modulus continues to rise [48,49].…”
Section: Mechanical Measurementsmentioning
confidence: 99%
“…GO causes rigidity enhancement of the PVA chain to restrict the movement of the molecular chains, leading to a high Young's modulus [46,47]. Tensile strength and elongation at break commonly drop after a certain weight percentage while the Young's modulus continues to rise [48,49].…”
Section: Mechanical Measurementsmentioning
confidence: 99%
“…In addition, various intelligent multi-functional fabrics with outstanding thermal management ability have also been reported in the literature. 15−17 One of the frequently reported strategies for producing thermal adhesives is to modify resins with thermal nanofillers, e.g., graphene, 18 boron nitride nanosheets (BNNSs), 19,20 and multi-walled carbon nanotubes (MWCNTs). 21 They possess ultrahigh specific surface area, excellent thermal properties, and unique micro topography, making them capable of effectively improving the thermal transfer ability of adhesive resins even under relatively low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Han and Elliott [22] studied the elastic behavior of CNT reinforced polymer nanocomposite and reported the elastic modulus as 94.6 GPa and 138.9 GPa for 12% and 17% volume fractions of CNT, respectively. Wang et al [24] studied the thermal conductivity and mechanical performance of boron nitride nanosheets (BNNS) based epoxy adhesives and found that addition of 1 wt% BNNS in epoxy enhances the Young's modulus, lap shear strength, fracture toughness and energy release rate by 69%, 31%, 122% and 118%, respectively. Lago et al [25] studied the dependence of the polycarbonate mechanical performances on boron nitride fakes morphology and observed the difference in Young's modulus of 56 MPa, being the increment, compared to pristine polycarbonate with 0.1 wt% of loading.…”
Section: Introductionmentioning
confidence: 99%